1995
DOI: 10.1002/j.1460-2075.1995.tb07062.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional studies of retroviral RNA pseudoknots involved in ribosomal frameshifting: nucleotides at the junction of the two stems are important for efficient ribosomal frameshifting.

Abstract: Ribosomal frameshifting, a translational mechanism used during retroviral replication, involves a directed change in reading frame at a specific site at a defined frequency. Such programmed frameshifting at the mouse mammary tumor virus (MMTV) gag‐pro shift site requires two mRNA signals: a heptanucleotide shifty sequence and a pseudoknot structure positioned downstream. Using in vitro translation assays and enzymatic and chemical probes for RNA structure, we have defined features of the pseudoknot that promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 46 publications
5
128
1
Order By: Relevance
“…Our data are consistent with a scenario where a local destabilization allows the elongating ribosome to unfold the distal pseudoknot-forming stem S2 before significant partitioning into the Ϫ1 reading frame. In fact, although the data are limited, the destabilization separating wild-type and C27A ScYLV RNAs is similar in magnitude to the degree to which the helical junction regions are destabilized in other frameshifting systems (⌬⌬G 37 Ϸ 1-2 kcal⅐mol Ϫ1 ) due to substitutions or deletions of junction nucleotides that negatively impact frameshift stimulation (24,28,29,40,48,49). Indeed, if the entire ground-state destabilization of mutant pseudoknots observed here (⌬⌬G 37 Ϸ 1.5 kcal⅐mol Ϫ1 ) is manifest as a decrease in the energy barrier to ribosome-promoted pseudoknot unwinding, ⌬⌬G ‡ , then this would translate into an Ϸ10-fold increase in the rate of unfolding in destabilized pseudoknots (14).…”
Section: Discussionmentioning
confidence: 92%
“…Our data are consistent with a scenario where a local destabilization allows the elongating ribosome to unfold the distal pseudoknot-forming stem S2 before significant partitioning into the Ϫ1 reading frame. In fact, although the data are limited, the destabilization separating wild-type and C27A ScYLV RNAs is similar in magnitude to the degree to which the helical junction regions are destabilized in other frameshifting systems (⌬⌬G 37 Ϸ 1-2 kcal⅐mol Ϫ1 ) due to substitutions or deletions of junction nucleotides that negatively impact frameshift stimulation (24,28,29,40,48,49). Indeed, if the entire ground-state destabilization of mutant pseudoknots observed here (⌬⌬G 37 Ϸ 1.5 kcal⅐mol Ϫ1 ) is manifest as a decrease in the energy barrier to ribosome-promoted pseudoknot unwinding, ⌬⌬G ‡ , then this would translate into an Ϸ10-fold increase in the rate of unfolding in destabilized pseudoknots (14).…”
Section: Discussionmentioning
confidence: 92%
“…The ratio of the two reporter proteins can be compared to determine the frequency of a frameshifting event. Frameshifting efficiency varies widely among pseudoknots, and altering the sequence of the pseudoknot can substantially affect the efficiency (24).…”
Section: Statement Of Purposementioning
confidence: 99%
“…Studies have found that thermodynamic stability of the pseudoknot is not correlated with frameshifting efficiency (24). That is, frameshifting and nonframeshifting structures have similar free energies.…”
Section: Statement Of Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Triple helix structures exist in yeast and human telomerase, and are found to be essential in quite a few biological processes (e.g. chromosome stability in stem cells, germline cells and cancer cells [8][9][10]; ribosomal frameshifting [11,12]). …”
Section: Introductionmentioning
confidence: 99%